2012
DOI: 10.1007/s00170-012-4647-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of CNC routing operations of wooden furniture parts

Abstract: The aim of this paper is to develop mathematical model and computational procedure for optimisation of feed rate at CNC routing operations of wooden furniture parts. The proposed approach takes into consideration special characteristics of solid wood, like changes in cutting forces and obtained surface quality along with cutting direction. A multistage optimisation procedure is developed, which employs binary search method and genetic algorithm. Because of the problem of full specification of feasible region i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 26 publications
(36 reference statements)
0
7
0
1
Order By: Relevance
“…The evaluation was then carried out to ensure buildability and optimization. The 3D model was revised to accommodate tolerances into joints in plywood and an additional cutting path was added to exclude the rounding of the tool bit out of the join slots (Figure 7) [61].…”
Section: Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation was then carried out to ensure buildability and optimization. The 3D model was revised to accommodate tolerances into joints in plywood and an additional cutting path was added to exclude the rounding of the tool bit out of the join slots (Figure 7) [61].…”
Section: Fabricationmentioning
confidence: 99%
“…out to ensure buildability and optimization. The 3D model was revised to accommod tolerances into joints in plywood and an additional cutting path was added to exclude rounding of the tool bit out of the join slots (Figure 7) [61]. The next stage consisted of flattening parts of the installation and nesting these ments onto 1525 × 1525 mm plywood sheets to minimize material waste (Figure 8) [ All the parts were numbered and placed on sheets according to the building schedul allow construction to start while other parts were being cut on the CNC plotter, there minimizing the time of construction.…”
Section: Fabricationmentioning
confidence: 99%
“…Processing parameters adjusted correctly are the most important factors that increase the surface quality of wood and wood-based boards (Koc et al, 2017). For this reason, many researchers have studied the effects of CNC processing parameters such as spindle rotational frequency, step over, feed rate, cutting tool diameter and depth of cut on surface roughness of solid wood (Gawronski, 2013 İşleyen and Karamanoğlu, 2019) processed with CNC machines. In general, it was found in these studies that higher values of spindle rotational frequency caused smoother surface of material whereas higher values of feed rate, step over and depth of cut resulted in the increased surface roughness of materials.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…In addition, surface roughness of wood affected by cutting machine and cutting parameters. Researchers have been reported that machine parameters affect surface roughness of wood and wood-based materials (Gawroński 2013, Sutcu 2013, Koc et al 2017. The anatomical properties of wood are not changeable, but the processing conditions can be adjusted to the desired range of operating parameters of the machine (Hazır and Koç 2019).…”
Section: Introductionmentioning
confidence: 99%